Seroprevalence and molecular epidemiology of EAST1 gene-carrying Escherichia coli from diarrheal patients and raw meats - Sukkua, Kannika; Manothong, Somruthai; Sukhumungoon, Pharanai (The Journal of Infection in Developing Countries, 2017)
Introduction: Several Escherichia coli pathotypes have been reported in Thailand; however, information on enteroaggregative heat-stable enterotoxin 1 (EAST1)-carrying E. coli (EAST1-EC) is insufficient. Previous reports show that consumption of raw meats causes diarrheagenic E. coli infections. In this study, we investigated the seroprevalence and genetic relationship of EAST1-EC from clinical and raw meat samples. Methodology: Diarrheal patients and raw meat samples were investigated for the presence of EAST1-EC by performing polymerase chain reaction (PCR) to detect astA. Serotyping, antimicrobial susceptibility tests, and PCR-based phylogenetic group assay were performed. Molecular epidemiology of E. coli strains from clinical and raw meat samples was determined using repetitive element-PCR typing, BOX-PCR, and ERIC2-PCR. Results: Results showed that 11.2% (17/152) of clinical samples and 53.3% (16/30) of raw meat samples had EAST1-EC. In all, 24 and 36 EAST1-EC strains were successfully isolated from 17 clinical and 16 raw meat samples, respectively. These strains had astA but did not possess the indicative genes of other E. coli pathotypes and were therefore classified as EAST1-EC. Most of these strains were multidrug resistant and were classified into nine serogroups. Molecular genotyping showed identical DNA fingerprint among EAST1-EC serotype O15 strains from clinical and raw chicken samples, suggesting that they were derived from the same bacterial clone. Conclusions: Our results indicated a high prevalence of multidrug-resistant EAST1-EC strains in clinical and environmental samples in Thailand belonging to nine serogroups. Moreover, the study highlighted the close association between infections caused by EAST1-EC serotype O15 and raw meat consumption.